Mortality in coeliac disease: a population-based cohort study from a single centre in Southern Derbyshire, UK. Issue 1 (17th April 2018) - Holmes, Geoffrey K T; Muirhead, Andrew
Abstract : Objective: With the advent of screening tests, it was hypothesised that milder cases of coeliac disease coming to diagnosis might have reduced risk of mortality. An earlier publication did not support this view. We have re-examined this issue employing a larger number of patients followed for a further 8 years. Design: Patients with coeliac disease from Southern Derbyshire, UK, were followed prospectively from 1978 to 2014 and included those diagnosed by biopsy and serology. Causes of death were ascertained. Standardised mortality ratios were calculated for all deaths, cardiovascular disease, malignancy, accidents and suicides, respiratory and digestive disease. Ratios were calculated for individual causes. Analysis centred on the postdiagnosis period that included follow-up time beginning 2 years from the date of coeliac disease diagnosis to avoid ascertainment bias. Patients were stratified according to date of diagnosis to reflect increasing use of serological methods. Results: All-cause mortality increase was 57%. Mortality in the serology era declined overall. Mortality from cardiovascular disease, specifically, decreased significantly over time. Death from respiratory disease significantly increased in the postdiagnosis period. The standardised mortality ratio for non-Hodgkin's lymphoma was 6.32, for pneumonia 2.58, for oesophageal cancer 2.80 and for liver disease 3.10. Survival in those who died after diagnosis increased by three times over the past three decades. Conclusions: Serological testing has impacted on the risk of mortality in coeliac disease. There is an opportunity to improve survival by implementing vaccination programmes for pneumonia and more prompt, aggressive treatments for liver disease.